Does your lab use social media? Sharing three years of experience in science communication - Pavlov, Alexey K.; Meyer, Amelie; Rösel, Anja; Cohen, Lana; King, Jennifer; Itkin, Polona; Negrel, Jean; Gerland, Sebastian; Hudson, Stephen R.; Dodd, Paul A.; de Steur, Laura; Mathisen, Stig; et al. (Bulletin of the American Meteorological Society, 2018)
Source at https://doi.org/10.1175/BAMS-D-17-0195.1 . © Copyright 27 June 2018 American Meteorological Society (AMS). Permission to use figures, tables, and brief excerpts from this work in scientific and educational works is hereby granted provided that the source is acknowledged. Any use of material in this work that is determined to be “fair use” under Section 107 of the U.S. Copyright Act or that satisfies the conditions specified in Section 108 of the U.S. Copyright Act (17 USC §108) does not require the AMS’s permission. Republication, systematic reproduction, posting in electronic form, such as on a website or in a searchable database, or other uses of this material, except as exempted by the above statement, requires written permission or a license from the AMS. All AMS journals and monograph publications are registered with the Copyright Clearance Center (http://www.copyright.com). Questions about permission to use materials for which AMS holds the copyright can also be directed to permissions@ametsoc.org. Additional details are provided in the AMS Copyright Policy statement, available on the AMS website (http://www.ametsoc.org/CopyrightInformation). Effective science communication is essential to share knowledge and recruit the next generation of researchers. Science communication to the general public can, however, be hampered by limited resources and a lack of incentives in the academic environment. Various social media platforms have recently emerged, providing free and simple science communication tools to reach the public and young people especially, an audience often missed by more conventional outreach initiatives. While individual researchers and large institutions are present on social media, smaller research groups are underrepresented. As a small group of oceanographers, sea ice scientists, and atmospheric scientists at the Norwegian Polar Institute, we share our experience establishing, developing, and maintaining a successful Arctic science communication initiative (@oceanseaicenpi) on ...